The relationship between sociodemographic characteristics of urban and rural areas with oral health service accessibility in Indonesia - Fuad H. Akbar; Burhanuddin D. Pasiga; Rasmidar Samad; Ayub I. Anwar; Nursyamsi Djamaluddin; Dewi Qalbiyani (DiscoverSys Inc., 2022)
Objective: the authors are interested in conducting a survey on the relationship of sociodemographic characteristics of urban and rural areas with the accessibility of OHS in Pinrang Districts, South Sulawesi, Indonesia in 2019. Material and Methods: This study used a qualitative approach by distributing questionnaires to adult subjects aged 18 years and above in Pinrang Districts, South Sulawesi during January 29th till February 1st, 2019. The location was divided according to the Pilot Pathfinder Survey method. The Urban area is represented by the Watang Sawitto Sub-District and the rural area is represented by the Suppa Sub-District. Results: The subjects who participated in this study were 298 people, an urban population (UP) was 184 people (61.74%) and a rural population (RP) was 114 people (38.26%). There is a significant relationship between sociodemographic characteristics and visits to oral health services (p=0.045). Community Health Center is the main choice if the subject has dental health problems. Conclusion: The main reason for visiting the oral health service facilities of the urban and rural population is for a tooth filling. Expensive cost and remote locations are the main reasons for not visiting oral health service facilities.